FAKTOR-FAKTOR YANG MEMPENGARUHI PURCHASE DECISION PADA HACHIO GUEST HOUSE AND CAFE - Daynestrie, Cindy Yosan; Khajar, Ibnu (Politeknik Negeri Ambon, 2025)
Introduction: A recent drop in sales revenue at Hachio Guest House and Cafe from January to February 2025 highlights the problem of declining sales. There is an emerging trend of challenges to consumers' purchasing decisions from Hachio Guest House and Cafe. This, therefore, makes it imperative for Hachio Guest House and Cafe to improve consumer repurchase decisions. This study discusses the effects of reputation and electronic word of mouth on repurchase decisions through trust. Further, this study's objective is to test the above-stated factors.Methods: This study will use a quantitative approach by testing hypotheses. The participants in this study are customers of Hachio Guest House and Cafe. A purposive sampling technique was used, with the rule that participants must be over 17 years old and have visited Hachio Guest House and Cafe at least once in the past six months, to select 150 participants using Maximum Likelihood Estimation. The analysis will use Structural Equation Modelling, with AMOS as the analytical tool to test the research hypotheses.Result: All hypotheses were accepted. This therefore means that reputation has a significant positive effect on trust, E-WOM also has a significant positive impact on trust, reputation has a noticeable positive effect on repurchase decision, E-WOM has a considerable influence in repurchase decision, and trust has a positive impact on repurchase decision. Keywords: Reputation, Electronic Word of Mouth, Trust, Repurchase Decision